SUPERVISION SYSTEM OF THE TRANSPORT AGENCY ON INTERCITY TRANSPORT IN THE PERSPECTIVE OF AL-HISBAH - Rina Rahmayana (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2021)
This study examines the supervision of the Aceh Provincial Department of Transportation (AKDP) from the perspective of the al-Hisbah concept, taking the Aceh Transportation Service as the object of study. Al-Hisbah is the most important form of monitoring economic life both internally and externally. The Department of Transportation is one of the al-Hisbah institutions. It has been involved in traffic control and transport, especially intercity transport within the province (AKDP). There are many problems associated with the development of official public transport. Intercity transport within the province (AKDP) is regulated by the government, especially the Ministry of Transport, one of the rules listed in the Minister of Transport Regulation (Permenhub) Number 15 of 2019 concerning the organisation of transport of people with public motor vehicles on routes. The purpose of this study was to find out the supervision system implemented by the Department of Transportation (AKDP) in Aceh, and to find out al-Hisbah's perspective on the supervision system implemented by the Department of Transportation (AKDP) in Aceh. The method used in this study, namely descriptive analysis method, using interview techniques, observation and documentation in the data collection process. The results of this study show that the Department of Transportation has supervised the intercity intra-provincial transport (AKDP) by making a draft activity plan in advance, so that later there will be no irregularities in the supervision.